Disability and socio-economic impact of mental disorders in the state of Punjab, India: Findings from national mental health survey, 2015–2016. (September 2018) - Chavan, BS; Das, Subhash; Garg, Rohit; Puri, Sonia; Banavaram, Aravind BA
Background: Mental illness results in a plethora of distressing issues, has tremendous socio-economic impact and causes socio-occupational dysfunction in the individual as well as the caregivers. There is a felt need to explore the disability caused by mental illness and the associated socio-economic impact at the population level in a developing nation like India. Aims: To elucidate the disability and socio-economic impact associated with mental illness at the individual and household levels for the state of Punjab in India. Method: This was a multisite cross-sectional study carried out during 2015–2016 (as a part of the National Mental Health Survey of India) in three districts and one urban metro area of Punjab. The sample was selected using multi-stage, stratified, random cluster sampling technique, with random selection based on Probability Proportionate to Size (PPS) at different stages. A validated set of questions was used to assess the socio-economic impact of mental illness and the Sheehan Disability Scale was used to document self-perceived disability among individuals with mental morbidity. Median (IQR) and proportions were used to summarize quantitative and qualitative data, respectively Results: Subjects with any mental morbidity reported disability of varying severities across different domains of life; family life was affected the most (70.1%). One in every six persons reported that their mental illness interfered with their daily activities to a large extent. Economic burden was high and a typical family would spend about INR 1500/month (US$23) towards the treatment of its member with mental morbidity. Family members had to forego their work for at least 7 days in 3 months to take care of their relative with mental illness. Conclusion: Mental illness causes disability in the individual and has tremendous socio-economic impact on the family, incapacitating a family's productivity to a large extent and thus affecting the society.